From classical to ultimate heat fluxes for convection at a vertical wall - Wells, AJ (Cambridge University Press, 2023)
Convection from a buoyancy source distributed over a vertical wall has diverse applications, from the natural ventilation of buildings to the melting of marine terminating glaciers which impact on future sea level. A key challenge involves determining how the rate and mechanisms of turbulent heat transfer should be extrapolated across a range of scales. Ke et al (J. Fluid Mech., vol. 964, 2023, A24) explore transitions in the turbulent flow dynamics using direct numerical simulation of a convective boundary layer at a heated vertical wall. A classical regime of heat transfer, consistent with previous laboratory experiments, gives way with increasing accumulation of buoyancy to an ultimate regime with enhanced heat transfer. The key to this transition lies in a near-wall sublayer, with a switch from laminar buoyancy-driven dynamics to a sublayer dominated by turbulence and shear instability from the mean flow.